Design of chitosan-based particle systems: A review of the physicochemical foundations for tailored properties - Ferreira, Leonardo M.B.; dos Santos, Aline M. [UNESP]; Boni, Fernanda Isadora [UNESP]; dos Santos, Karen C. [UNESP]; Robusti, Leda M. Gorla [UNESP]; de Souza, Maurício P.C. [UNESP]; Ferreira, Natália N. [UNESP]; Carvalho, Suzana G. [UNESP]; Cardoso, Valéria M.O. [UNESP]; Chorilli, Marlus [UNESP]; Cury, Beatriz S.F. [UNESP]; de Godoi, Denis R.M. [UNESP]; et al. (Elsevier, 2020)
Chitosan-based particles are widely proposed as biocompatible drug delivery systems with mucoadhesive and permeation enhancing properties. However, strategies on how to modulate the intended biological responses are still scarce. Considering that particle properties affect the biological outcome, the rational design of the synthesis variables should be proposed to engineer drug delivery systems with improved biological performance. The purpose of this review is to establish a deeper understanding of possible correlations between these variables and the particle properties from theoretical and experimental perspectives. The fundamental physicochemical knowledge of chitosan-based polyelectrolyte complexation and surface modification is discussed focusing on chitosan-TPP, polyelectrolyte complexes, and chitosan-surface modified PLGA or lipid particles. A set of design considerations is proposed to enable future investigation in the development of chitosan particles with modulated properties. The approach presented here contributes to the rational design of chitosan-based particles that meet different requirements for biological activities.
Keywords: Chitosan particles; Polysaccharides; Rational design; Self-assembly; Supramolecular chemistry; Thermodynamics